Long-term effects of early adversity on the mental health of college students: The mitigating effect of physical exercise - Wang, Xinzhu; Fu, Kaixian (Frontiers in Psychology, 2023)
Background: We aim to investigate the long-term effects of early adversity on university students’ mental health and the mitigating effect of physical exercise on this effect. Methods: The survey sample consisted of 895 college students. Descriptive statistics, linear regression, and moderating effect analysis were used to analyze the results. Results: (1) Early adversity negatively predict mental health level (β = -0.109, t = -4.981, p < 0.01); (2) Physical exercise can effectively mitigate the long-term harm of early adversity to mental health (β = 0.039，t = 2.001, p < 0.05); compared to low-level physical exercise (bsimple = -0. 067，t = -7.88, p < 0.01), high-level physical exercise can mitigate the long-term harm of early adversity to mental health (bsimple = -0. 025, t = -2. 37, p < 0.01). Conclusion: Early adversity affects the mental health of university students, but physical exercise can effectively mitigate this effect.